“Sound Horeg” dan pembacaan oposisional: Analisis konten Instagram @malangraya_info dalam memaknai sound horeg - Sufa, Fauziah Arfayati; Pradhipta, Amelia Yeza (Jurnal Mahasiswa Komunikasi Cantrik, 2025)
This study analyzes audience reception of the “sound horeg” phenomenon as public speaker-based entertainment in public spaces, sparking debate. The purpose of this study is to understand how the audience interprets “sound horeg” as a form of community entertainment. The research uses a qualitative method. Data were obtained from Instagram user comments on three posts: October 26, 2024, September 22, 2024, and October 28, 2024. The study's results on the “sound horeg” phenomenon, as reported by the account @malangraya_info, indicate that oppositional reading is the most common reception. This study not only highlights that audiences actively interpret media messages based on their individual cultural and social backgrounds, but also that the “sound horeg” phenomenon is predominantly rejected by audiences.